2013
DOI: 10.3390/ijms141122933
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver: A Possible New Target for Type 2 Diabetes Prevention and Treatment

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common liver disorder worldwide. Several lines of evidence have indicated a pathogenic role of insulin resistance, and a strong association with type 2 diabetes (T2MD) and metabolic syndrome. Importantly, NAFLD appears to enhance the risk for T2MD, as well as worsen glycemic control and cardiovascular disease in diabetic patients. In turn, T2MD may promote NAFLD progression. The opportunity to take into account NAFLD in T2MD prevention and care has stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 184 publications
(196 reference statements)
0
69
0
4
Order By: Relevance
“…In this context, it has be hypothesized that NAFLD may be considered as a new target for T2DM prevention and treatment [9] .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it has be hypothesized that NAFLD may be considered as a new target for T2DM prevention and treatment [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the fermentation-induced changes in anthocyanin composition appear to change how the anthocyanins alter glucose metabolism in estrogen-deficient animals. Hepatic steatosis may be associated with oxidative hepatocellular damage, inflammation, activation of fibrogenesis, and systemic insulin resistance (Fruci et al 2013). The present study found that BCAO decreased hepatic fat storage mainly by increasing fatty acid oxidation and decreasing lipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin is used in the treatment of type 2 diabetes and has been investigated for other diseases in which insulin resistance might be an important factor, such as NAFLD [26] . In the present study, we used metformin as a positive control drug during the experiment.…”
Section: Discussionmentioning
confidence: 99%